Pattern Of Induced Oestrus And Conception Rate Following Ovsynch Programme In Post-Partum Dairy Cows - Velladurai, C.; Napolean, R. Ezakial; Selvaraju, M.; Doraisamy, K.A. (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
Sixteen normally calved cows were selected at 35-50 days postpartum and equally divided into two groups as group I and II. All the cows were orally supplemented daily with 30-50 grams of TANUVAS mineral mixture continuously for 15 days. Group I cows were treated with ovsynch protocol between days 50 and 65 post-partum. Oestrus response, mean interval to onset of induced oestrus, duration of oestrus and ovulatory response in group I were 100 per cent, 47.97±2.65 hours, 29.84±0.67 hours and 100 per cent and the corresponding values in group II were 75.00 per cent, 23.50±4.24 days, 28.78±0.67 hours and 62.50 per cent, respectively. The percentage of intense oestrus intensity was higher in group I than group II cows. The first service, second service and overall conception rate observed were 37.50, 50.00 and 87.50 per cent in group I and 25.00, 37.50 and 62.50 per cent in group II cows, respectively.